PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE ANIMATE TEMA SICH VORSTELLEN UNTUK KETERAMPILAN MEMBACA SISWA KELAS X - Bintari, Dianty Putri; Pujosusanto, Ari (LATERNE, 2025)
This research was conducted based on the need for innovative and interactive learning media in teaching German for tenth-grade students, particularly on the theme Sich Vorstellen. Based on interviews with the German language teacher at SMAN 15 Surabaya, it was found that students still struggle to understand reading texts in German. This situation indicated the necessity of developing learning media that could support the improvement of students’ reading skills. The aim of this study was to design and develop interactive learning media using Adobe Animate on the Sich Vorstellen topic, as well as to evaluate its feasibility as a learning tool. The research approach used was the Research and Development (R&D) method by adapting three stages from the Dick and Carey development model: analysis, design, and development. Data collection was carried out through validation sheets completed by subject matter experts and media experts. The results of the feasibility test show that the developed learning media received a score of 94% from the subject matter expert and 94.67% from the media expert. These results indicated that the interactive learning media based on Adobe Animate was highly feasible for supporting the reading skills of tenth-grade students in German language learning.